Реєстрація електроміографічних біопотенціалів на базі мікроконтролерної системи - Малахова, О. Ю.; Чумак, В. С. (ХНУРЕ, 2022)
This paper considers the theoretical aspects of using a microcontroller system for recording electromyographic potentials. Characterizing the biopotentials obtained during the myographic study. The functional value of the microcontroller in the registration of electromyographic biopotential, the main technical characteristics that should be considered when choosing a microcontroller. Areas and prospects for the use of microcontrollers in the registration of biological activity of muscles are considered.
Keywords: ЕМГ; біопотенціал